Bi(OTf)3 Enabled C-F Bond Cleavage in HFIP: Electrophilic Aromatic Formylation with Difluoro(phenylsulfanyl)methane - Nolan M. Betterley (2019)
© 2018 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim Bismuth(III) trifluoromethanesulfonate [Bi(OTf)3] mediated mild electrophilic aromatic formylation utilizing difluoro(phenylsulfanyl)methane (PhSCF2H) as a formylating agent in hexafluoro-2-propanol (HFIP) as a recyclable ionizing solvent has been developed. The active formylating species was generated via C−F bond cleavage and was characterized to be a bis(phenylsulfanyl)methyl cation by experimental and computational 1H and 13C NMR.